Pengaruh Model Pembelajaran Discovery Learning terhadap Hasil Belajar Matematika Kelas V SD Kurikulum Merdeka Belajar - Rahma Taher; Yanti Fitria; Risda Amini (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2023)
Abstract: The teacher-centered learning process forms a monotonous teaching and learning process, and low student mathematics learning outcomes. Educators must use innovative and creative learning models to improve student learning outcomes. Discovery Learning learning model is a learning model that forms active students in finding, solving a problem. In its application, students are asked to be able to discover mathematical principles and concepts through independent learning processes. This research uses a quantitative approach (Quantitative Approach). The research design was a pretest-posttest control group design. This research was conducted on fifth grade students at SD Negeri 13 Simpang Haru, which is located in the East Padang District, Padang City, West Sumatra. Data analysis techniques are in the form of descriptive analysis techniques consisting of prerequisite tests in the form of normality tests, homogeneity tests, and hypothesis testing using different tests or T-tests (T-Test). The results of this study indicate that there is a significant influence in the application of the Discovery Learning model compared to the direct teaching model on the mathematics learning outcomes of fifth grade students at SD Negeri 13 Simpang Haru, Padang City (p<0.05). Keywords: Discovery Learning, Learning Outcomes, Independent Learning Curriculum